CASTLE OF AYAZ KALA - Xurliman Aytmuratova; Anar Bazarbaeva; Sayora Erejepova (Journal Park Publishing, 2023)
The article mainly contains information about the Ayaz fortress, which century it belongs to, and at the same time, its influence on the life of the people living in this area.